Uterine artery flow velocity waveform, arterial flow indices, follicular dynamics, and sex hormones during preovulatory period in synchronized ovulatory cycle of Bos indicus beef cows - Tossapol Moonmanee (2018)
© 2018 Society for Biology of Reproduction & the Institute of Animal Reproduction and Food Research of Polish Academy of Sciences in Olsztyn A greater understanding of the uterine artery's (UtA) biology is essential to the increase in female reproductive abilities. The UtA flow velocity waveform, blood flow volume (BFV), pulsatility and resistance indices (PI and RI), blood flow velocities, dynamics of the dominant follicle (DF), and estradiol (E2) and progesterone (P4) levels in an induced ovulatory cycle were evaluated in Thai native cattle. Twenty cows were induced with synchronized ovulation through a P4-releasing device, from Day −9 to Day −4, concurrent with the administration of two doses of a gonadotropin-releasing hormone on Day −9 and Day −1, and two doses of prostaglandin F2αon Day −4 and 8 h later. Day 0 was designated as the day of ovulation. The cows underwent Doppler sonographic determination and blood collection from Day −4 to Day 0. The cows were classified in the non-ovulating (n = 5) and ovulating groups (n = 15). The ovulating cows presented higher BFV values, blood flow velocities, DF growth rates, and E2 levels; yet lower PI values and P4 concentrations, than those of the non-ovulating cows. The BFV values and the blood flow velocities were greater, but the RI and PI values were lower in the ovulatory side UtA than in the contraovulatory side UtA. The BFV values were positively correlated with blood flow velocities, DF growth rates and E2 concentrations in the ovulating cows; confirming the importance of UtA blood flow, follicular growth, and E2-vasodilation during preovulatory phase in the induced ovulatory cycle of Bos indicus beef cows.